Model Pengawasan Lembaga Pengumpul Dana Sosial pada Yayasan Dompet Dhuafa: Perspektif Hukum Positif dan Mazhab al-Syafi’i - Majid, Afirah; Mustafa, Zulhasari; Ramli, Arif Rahman; Lukman, Atriani (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Dompet dhuafa as a fund collector who has obtained an operational license from the Social Welfare Institute needs to be monitored so that misappropriation does not occur. The main point of this study is the analysis of the supervision model in the social fund collection institution dompet dhuafa in the perspective of positive law and Imam Shafi'i. The purpose of this study is to find out how the supervision of social fund collectors of poor wallets in the perspective of positive law and Imam Shafi'i. This type of research uses qualitative methods. Data is the result of interviews sourced from Dompet Dhuafa employees. The analysis technique used is positive legal analysis by examining library materials, namely regulations and literature related to the problem under study, and Shafi'i School analysis related to the implementation of supervision based on Islamic law, both from the Qur'an, al-Hadith, the rules of Usul Fiqh and the opinions of scholars. The results showed that Dompet Dhuafa Makassar has four supervisory systems, the first of which is the Sharia Advisory Board which is tasked with determining the policies to be carried out by the institution, then an internal audit from the head office of Dompet Dhuafa, an external audit from a Public Accounting Firm, and an Audit of the Ministry of Religion and BAZNAS where the three supervisions examine the financial statements of the institution. In the analysis of the Shafi'i school the context of supervision in institutions as well as ar-riqobah is an obligation that must be resolved continuously, because supervision is to examine the way of making plans in an institution to avoid failure.